PROGRAM APLIKASI INVENTORI PADA PD PRIMA JAYA - Arleine Arleine; Ery Dewayani; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
PD Prima Jaya is a family Company which is sell materials like Batako, Bata Merah, and Hebel. PD Prima Jaya have a difficulty for recording data in and out because in a day they can sell many pieces of Batako, Bata Merah and Hebel. So it will be make an inventory application program for recording data in and out for PD Prima Jaya. The programming using SDLC method, betwixt the investigative stage, the analysis phase, design phase, and implementation phase. The programming language using Visual Basic 2012 and for Database using SQL Server 2012 Management Server. Inventory Application Program for PD Prima Jaya has been created so that admin can find out information about recording data in and out, can find out a best seller materials in a month.